164 SUSTAINED SECONDARY HYPERPARATHYROIDISM AND THE RECOVERY OF FALLEN EXTRACELLULAR CALCIUM AND MAGNESIUM IN RATS WITH CHRONIC ALDOSTERONISM. (1st January 2006) - Thomas, M.; Vidal, A.; Bhattacharya, S. K.; Sun, Y.; Weber, K. T.
Abstract : Purpose: Congestive heart failure (CHF) has its origins rooted in an activation of the circulating renin-angiotensin-aldosterone system. In patients with protracted CHF of 4 wks or more, where chronic aldosteronism is contributory to their salt-avid state, we found ionized hypocalcemia and hypomagnesemia together with elevations in serum parathyroid hormone (PTH). In a rat model of chronic aldosteronism (ALDOST), extracellular concentrations of these divalent cations are reduced in response to an early and persistent increase in both urinary and fecal excretion. The resultant secondary hyperparathyroidism (SHPT) and continual PTH-mediated resorption of bone is invoked to restore homeostasis of these cations. Bone Ca and Mg are each reduced by 10% at 4 wks and more than 40% at 6 wks of ALDOST with a corresponding fall in bone strength to flexor stress. The time course to the restoration of fallen plasma Ca and Mg that accompanies SHPT in rats with ALDOST remains uncertain. Methods: Toward this end, we monitored plasma total Ca and Mg and PTH in uninephrectomized rats with 1, 4, and 6 weeks ALDOST generated by aldosterone infusion (0.75 μg/h, by implanted minipump; and 1% NaCl/0.4% KCl in drinking water), without or with prior parathyroidectomy (PTx). Results: In rats with ALDOST and intact parathyroids, plasma PTH was increased (p < .05) at weeks 1, 4, and 6 (87 6 11, 75 6 13, and 78 6 15 pg/mL, respectively) compared to controls (53 6 7 pg/mL), which was abrogated by PTx. This SHPT appeared in response to a decline (p < .05) in plasma Ca at weeks 1 and 4 (7.06 6 0.17 and 7.85 6 0.22 mg/dL), which was restored at week 6 (8.22 6 0.22 mg/dL) to control levels (8.47 6 0.07 mg/dL). A similar time course to the decline and subsequent normalization of plasma Mg was found. In rats with ALDOST + PTx, an early (p < .05) and persistent (p < .05) hypocalcemia and hypomagnesemia accompanied 1-6 weeks of ALDOST. Conclusions: In rats with chronic aldosteronism, accompanied by hypocalcemia and hypomagnesemia, sustained SHPT is required to restore Ca and Mg homeostasis. These findings suggest that supplemental Ca, Mg, and vitamin D may be required to minimize SHPT and preserve Ca and Mg balance in patients with protracted CHF.